Hippocampal “cholinergic interneurons” visualized with the choline acetyltransferase promoter: anatomical distribution, intrinsic membrane properties, neurochemical characteristics, and capacity for cholinergic modulation - Yi, Feng; Catudio-Garrett, Elizabeth; Gábriel, Robert; Wilhelm, Marta; Erdelyi, Ferenc; Szabo, Gabor; Deisseroth, Karl; Lawrence, Josh (Frontiers in Synaptic Neuroscience, 2015)
Release of acetylcholine (ACh) in the hippocampus (HC) occurs during exploration, arousal, and learning. Although the medial septum-diagonal band of Broca (MS-DBB) is the major extrinsic source of cholinergic input to the HC, cholinergic neurons intrinsic to the HC also exist but remain poorly understood. Here, ChAT-tauGFP and ChAT-CRE/Rosa26YFP (ChAT-Rosa) mice were examined in HC. The HC of ChAT-tauGFP mice was densely innervated with GFP-positive axons, often accompanied by large GFP-positive structures, some of which were Neurotrace/DAPI-negative and likely represent large axon terminals. In the HC of ChAT-Rosa mice, ChAT-YFP cells were Neurotrace-positive and more abundant in CA3 and dentate gyrus than CA1 with partial overlapping with calretinin/VIP. Moreover, an anti-ChAT antibody consistently showed ChAT immunoreactivity in ChAT-YFP cells from MS-DBB but rarely from HC. Furthermore, ChAT-YFP cells from CA1 stratum radiatum/stratum lacunosum moleculare (SR/SLM) exhibited a stuttering firing phenotype but a delayed firing phenotype in stratum pyramidale (SP) of CA3. Input resistance and capacitance were also different between CA1 SR/LM and CA3 SP ChAT-YFP cells. Bath application of ACh increased firing frequency in all ChAT-YFP cells; however, cholinergic modulation was larger in CA1 SR/SLM than CA3 SP ChAT-YFP cells. Finally, CA3 SP ChAT-YFP cells exhibited a wider AP half-width and weaker cholinergic modulation than YFP-negative CA3 pyramidal cells. Consistent with CRE expression in a subpopulation of principal cells, optogenetic stimulation evoked glutamatergic postsynaptic currents in CA1 SR/SLM interneurons. In conclusion, the presence of fluorescently labeled hippocampal cells common to both ChAT-Rosa and ChAT-tauGFP mice are in good agreement with previous reports on the existence of cholinergic interneurons, but both transgenic mouse lines exhibited unexpected anatomical features that departed considerably from earlier observations.